The Influence of Leadership Style, Work Motivation and Organizational Commitment on the Performance of the United Development Party Management of the Regional Leadership Council of South Sulawesi Province - Insyan Khairy Fahry; Andi Jam’an; Dg Makkalassa (Journal AGENCY, 2025)
This research aims to determine the influence of leadership style, work motivation and organizational commitment on the performance of the development party management of the Regional Leadership Council of South Sulawesi Province. The population in this study was members of the South Sulawesi Province Regional Leadership Council development party, as many as 52 administrators with the sample determined using a saturated sampling formula so that 52 samples were obtained. The type of research used is a quantitative method with an explanatory approach. The data used is primary data using questionnaire techniques. The data analysis methods used are instrument testing: validity test and reliability test, normality test, classical assumption test: multicollinearity test and heteroscedasticity test, multiple linear regression analysis, hypothesis testing: simultaneous test, partial test and coefficient of determination. From the simultaneous research results obtained The results show that leadership style, motivation and organizational commitment have a significant effect on management performance, from partial results the leadership style variable has a positive effect on management performance, the work motivation variable has a positive effect on management performance, and organizational commitment has no positive effect on management performance